Soil C:N ratio as a predictor of annual riverine DOC flux at local and global scales - Aitkenhead, J. A.; McDowell, W. H. (Global Biogeochemical Cycles, 2000)
Keywords: 1615 Biogeochemical cycles, processes, and modeling 1806 Chemistry of fresh water 1871 Surface water quality

Methane Flux from Mississippi River Deltaic Plain Wetlands - Alford, Douglas P.; Delaune, Ronald D.; Lindau, Charles W. (Biogeochemistry, 1997)

Variation of Energy and Carbon Fluxes From a Restored Temperate Freshwater Wetland and Implications For Carbon Market Verification Protocols - Anderson, F. E.; Bergamaschi, B.; Sturtevant, C.; Knox, S.; Hastings, L.; Windham-Myers, L.; Detto, M.; Hestir, E. L.; Drexler, J.; Miller, R. L.; Matthes, J. H.; Verfaillie, J.; et al. (Journal of Geophysical Research: Biogeosciences, 2016)
Keywords: wetlands eddy covariance carbon dioxide methane carbon market global warming potential san-joaquin delta dissolved organic-carbon path gas analyzers methane emission eddy covariance dioxide exchange co2 flux ecosystem respiration peatland restoration primary productivity

Biotic and Abiotic Factors Interact To Regulate Northern Peatland Carbon Cycling - Armstrong, Alona; Waldron, Susan; Ostle, Nicholas J.; Richardson, Harriett; Whitaker, Jeanette (Ecosystems, 2015)

Greenhouse Gas Emissions and Carbon Sequestration Potential in Restored Wetlands of the Canadian Prairie Pothole Region - Badiou, P.; McDougal, R.; Pennock, D.; Clark, B. (Wetlands Ecology and Management, 2011)
Keywords: carbon sequestration greenhouse gas emissions methane prairie pothole wetlands methane emission phragmites-australis emergent macrophytes typha-latifolia organic-matter soils sediment fluxes cycle

Tillage and Soil Carbon Sequestration—What Do We Really Know? - Baker, John M.; Ochsner, Tyson E.; Venterea, Rodney T.; Griffis, Timothy J. (Agriculture, Ecosystems and Environment, 2007)

Temperature and Hydrology Affect Methane Emissions From Prairie Pothole Wetlands - Bansal, Sheel; Tangen, Brian; Finocchiaro, Ray (Wetlands, 2016)

Methane emissions along a salt marsh salinity gradient - Bartlett, Karen B.; Bartlett, David S.; Harriss, Robert C.; Sebacher, Daniel I. (Biogeochemistry, 1987)

Review and assessment of methane emissions from wetlands - Bartlett, Karen B.; Harriss, Robert C. (Chemosphere, 1993)

Methane flux from coastal salt marshes - Bartlett, Karen B.; Harriss, Robert C.; Sebacher, Daniel I. (Journal of Geophysical Research: Atmospheres, 1985)
Keywords: 0315 Biosphere/atmosphere interactions 0330 Geochemical cycles 4235 Estuarine processes

Soil Organic Carbon Stocks Under Native Vegetation - Revised Estimates For Use With the Simple Assessment Option of the Carbon Benefits Project System - Batjes, N. H. (Agriculture, Ecosystems and Environment, 2011)
Keywords: carbon benefits project ipcc guidelines climate zone soil classes soil carbon stocks native vegetation uncertainty land-use climate-change world sequestration uncertainty nitrogen database storage matter brazil

Soil Greenhouse Gas Emissions and Carbon Budgeting in a Short-hydroperiod Floodplain Wetland - Batson, J.; Noe, G. B.; Hupp, C. R.; Krauss, K. W.; Rybicki, N. B.; Schenk, E. R. (Journal of Geophysical Research: Biogeosciences, 2015)
Keywords: carbon greenhouse gases floodplain riparian geomorphology hydrologic connectivity fresh-water wetlands coastal-plain rivers south-eastern australia methane emissions phosphorus mineralization northern wetlands dioxide exchange ch4 emissions nitrous-oxide forest stands

Interactive Effects of Vegetation, Soil Moisture and Bulk Density On Depth of Burning of Thick Organic Soils - Benscoter, B. W.; Thompson, D. K.; Waddington, J. M.; Flannigan, M. D.; Wotton, B. M.; de Groot, W. J.; Turetsky, M. R. (International Journal of Wildland Fire, 2011)

Micro-scale CO2 and CH4 dynamics in a peat soil during a water fluctuation and sulfate pulse - Blodau, C.; Moore, T. R. (Soil Biology and Biochemistry, 2003)

A global wetland methane emissions and uncertainty dataset for atmospheric chemical transport models (WetCHARTs version 1.0) - Bloom, A. Anthony; Bowman, Kevin W.; Lee, Meemong; Turner, Alexander J.; Schroeder, Ronny; Worden, John R.; Weidner, Richard; McDonald, Kyle C.; Jacob, Daniel J. (Geoscientific Model Development, 2017)

Net ecosystem CO2 exchange in a temperate cattail marsh in relation to biophysical properties - Bonneville, Marie-Claude; Strachan, Ian B.; Humphreys, Elyn R.; Roulet, Nigel T. (Agricultural and Forest Meteorology, 2008)

Net Ecosystem Production and Carbon Greenhouse Gas Fluxes in Three Prairie Wetlands - Bortolotti, Lauren E.; St. Louis, Vincent L.; Vinebrooke, Rolf D.; Wolfe, Alexander P. (Ecosystems, 2015)

Methane Emissions From Wetlands: Biogeochemical, Microbial, and Modeling Perspectives From Local To Global Scales - Bridgham, S. D.; Cadillo-Quiroz, H.; Keller, J. K.; Zhuang, Q. (Global Change Biology, 2013)
Keywords: Bacteria/*metabolism Biota Methane/*analysis/metabolism Models, Theoretical *Soil Microbiology *Wetlands

Wetlands - Bridgham, S.D.; J.P. Megonigal; J.K. Keller; N.B. Bliss; Trettin, C. (The First State of the Carbon Cycle Report (SOCCR): The North American Carbon Budget and Implications for the Global Carbon Cycle. A Report by the U.S. Climate Change Science Program and the Subcommittee on Global Change Research., 2007)

The Carbon Balance of North American Wetlands - Bridgham, Scott D.; Megonigal, J. Patrick; Keller, Jason K.; Bliss, Norman B.; Trettin, Carl (Wetlands, 2006)

Mechanisms Controlling Soil Respiration (CO2 and CH4) in Southern Peatlands - Bridgham, Scott D.; Richardson, Curtis J. (Soil Biology and Biochemistry, 1992)

Effects of Impoundment On Vertical Accretion of Coastal Marsh - Bryant, John C.; Chabreck, Robert H. (Estuaries, 1998)

Effects of physical, chemical and botanical characteristics of peat on carbon gas fluxes - Buttler, A.; Dinel, H.; Levesque, P. E.M. (Soil Science, 1994)

The Federal Policy On Wetland Conservation - Canadian Wildlife Service (Minister of Environment, Minister of Supply and Services Canada, 1991)

Global Carbon Exchange and Methane Emissions From Natural Wetlands: Application of a Process-based Model - Cao, Mingkui; Marshall, Stewart; Gregson, Keith (Journal of Geophysical Research: Atmospheres, 1996)

Los Humedales En Mexico: Tendencias Y Oportunidades - Casasola, P. M. (Cuadernos de biodiversidad, 2008)

The First State of the Carbon Cycle Report (SOCCR): the North American Carbon Budget and Implications For the Global Carbon Cycle. a Report By the U.S. Climate Change Science Program and the Subcommittee On Global Change Research - CCSP (National Oceanic and Atmospheric Administration, National Climatic Data Center, Asheville, NC, USA, 242 pp., 2007)

Reconciling Carbon-cycle Concepts, Terminology, and Methods - Chapin, F. S.; Woodwell, G. M.; Randerson, J. T.; Rastetter, E. B.; Lovett, G. M.; Baldocchi, D. D.; Clark, D. A.; Harmon, M. E.; Schimel, D. S.; Valentini, R.; Wirth, C.; Aber, J. D.; et al. (Ecosystems, 2006)
Keywords: net ecosystem production net ecosystem carbon balance gross primary production ecosystem respiration autotrophic respiration heterotrophic respiration net ecosystem exchange net biome production net primary production terrestrial ecosystems atmospheric co2 organic-carbon primary productivity energy-flow salt-marsh metabolism forests climate photosynthesis

An Overview of Peatland Restoration in North America: Where Are We After 25 Years? - Chimner, Rodney A.; Cooper, David J.; Wurster, Frederic C.; Rochefort, Line (Restoration Ecology, 2016)

Climatic variability, hydrologic anomaly, and methane emission can turn productive freshwater marshes into net carbon sources - Chu, Housen; Gottgens, Johan F.; Chen, Jiquan; Sun, Ge; Desai, Ankur R.; Ouyang, Zutao; Shao, Changliang; Czajkowski, Kevin (Global Change Biology, 2015)
Keywords: carbon budget carbon dioxide carbon sequestration dissolved organic carbon eddy-covariance methane particulate organic carbon

Current systematic carbon-cycle observations and the need for implementing a policy-relevant carbon observing system - Ciais, P.; Dolman, A. J.; Bombelli, A.; Duren, R.; Peregon, A.; Rayner, P. J.; Miller, C.; Gobron, N.; Kinderman, G.; Marland, G.; Gruber, N.; Chevallier, F.; et al. (Biogeosciences, 2014)
BG

Variations in discharge and dissolved organic carbon and nitrogen export from terrestrial basins with changes in climate: A neural network approach - Clair, Thomas A.; Ehrman, James M. (Limnology and Oceanography, 1996)

Exports of carbon and nitrogen from river basins in Canada's Atlantic Provinces - Clair, T. A.; Pollock, T. L.; Ehrman, J. M. (Global Biogeochemical Cycles, 1994)
Keywords: 1806 Chemistry of fresh water 1824 Geomorphology: general 1833 Hydroclimatology 4239 Limnology

Evaluation of ALOS PALSAR Data For High-Resolution Mapping of Vegetated Wetlands in Alaska - Clewley, D.; Whitcomb, J.; Moghaddam, M.; McDonald, K.; Chapman, B.; Bunting, P. (Remote Sensing, 2015)
Keywords: land-cover database methane emissions inventory maps random forests climate-change classification succession impacts project extent

Classification of Wetlands and Deepwater Habitats of the United States - Cowardin, L. M.; Carter, V.; Golet, F. C.; LaRoe, E. T. (1979)

Methane flux from Minnesota Peatlands - Crill, P. M.; Bartlett, K. B.; Harriss, R. C.; Gorham, E.; Verry, E. S.; Sebacher, D. I.; Madzar, L.; Sanner, W. (Global Biogeochemical Cycles, 1988)
Keywords: 0315 Biosphere/atmosphere interactions 0330 Geochemical cycles 9350 North America

Wetlands Losses in the United States: 1780's To 1980's - Dahl, T. E. (1990)

Status and trends of wetlands in the conterminous United States 2004 to 2009 - Dahl, Thomas E (US Department of the Interior, US Fish and Wildlife Service, Fisheries and Habitat Conservation, 2011)

Status and Trends of Prairie Wetlands in the United States 1997 To 2009 - Dahl, T. E. (2014)

Effect of Assessment Scale On Spatial and Temporal Variations in CH4, CO2, and N2O Fluxes in a Forested Wetland - Dai, Z. H.; Trettin, C. C.; Li, C. S.; Li, H.; Sun, G.; Amatya, D. M. (Water Air and Soil Pollution, 2012)
Keywords: forest-dndc forested wetland greenhouse gases carbon cycling systeme hydrologique europeen distributed modeling system nitrous-oxide evolution process-oriented model mike she model carbon dynamics rainfall events south-carolina climate-change coastal-plain

Productivity and nutrient export studies in a cypress swamp and lake system in Louisiana - Day, J. W.; T. J. Butler; Conner, W . H. (Estuarine Processes. vol. 2,, 1977)

Threats, Conservation Actions, and Research Within 78 Mexican Non-coastal Protected Wetlands - De Gortari-Ludlow, Natalia; Espinosa-Reyes, Guillermo; Flores-Rivas, Joel; Salgado-Ortiz, Javier; Chapa-Vargas, Leonardo (Journal for Nature Conservation, 2015)

Landscape-level Terrestrial Methane Flux Observed From a Very Tall Tower - Desai, Ankur R.; Xu, Ke; Tian, Hanqin; Weishampel, Peter; Thom, Jonathan; Baumann, Dan; Andrews, Arlyn E.; Cook, Bruce D.; King, Jennifer Y.; Kolka, Randall (Agricultural and Forest Meteorology, 2015)

Effects of Elevated Carbon Dioxide and Increased Temperature On Methane and Nitrous Oxide Fluxes: Evidence From Field Experiments - Dijkstra, F. A.; Prior, S. A.; Runion, G. B.; Torbert, H. A.; Tian, H. Q.; Lu, C. Q.; Venterea, R. T. (Frontiers in Ecology and the Environment, 2012)
Keywords: trace gas fluxes atmospheric co2 enrichment ecosystem responses shortgrass steppe north-america spruce forest soil n2o ch4 emissions

Methane Emission from Natural Wetlands in China: Summary of Years 1995–2004 Studies - Ding, Wei-Xin; Cai, Zu-Cong (Pedosphere, 2007)

Winter fluxes of methane from Minnesota peatlands - Dise, Nancy B (Biogeochemistry, 1992)

Methane emission from Minnesota peatlands: Spatial and seasonal variability - Dise, Nancy B. (Global Biogeochemical Cycles, 1993)
Keywords: 0330 Geochemical cycles 0315 Biosphere/atmosphere interactions

Suppression of peatland methane emission by cumulative sulfate deposition in simulated acid rain - Dise, Nancy B.; Verry, Elon S. (Biogeochemistry, 2001)

The Legacy of Wetland Drainage On the Remaining Peat in the Sacramento — San Joaquin Delta, California, USA - Drexler, Judith Z.; Fontaine, Christian S.; Deverel, Steven J. (Wetlands, 2009)

A Long-Term Comparison of Carbon Sequestration Rates in Impounded and Naturally Tidal Freshwater Marshes Along the Lower Waccamaw River, South Carolina - Drexler, J. Z.; Krauss, K. W.; Sasser, M. C.; Fuller, C. C.; Swarzenski, C. M.; Powell, A.; Swanson, K. M.; Orlando, J. (Wetlands, 2013)
Keywords: carbon sequestration impounded tidal freshwater marsh vertical accretion san-joaquin delta sediment accumulation nutrient accumulation vertical accretion plant community pb-210 wetlands fluxes hydrology balance

Chapter 2: Drained Inland Organic Soils. Supplement to the 2006 IPCC Guidelines for National Greenhouse Gas Inventories: Wetlands. - Drösler, M.; L.V. Verchot; A. Freibauer; Pan, G. (Intergovernmental Panel on Climate Change , Switzerland, 2014)

Sediment Accretion in Tidal Freshwater Forests and Oligohaline Marshes of the Waccamaw and Savannah Rivers, USA - Ensign, Scott H.; Hupp, Cliff R.; Noe, Gregory B.; Krauss, Ken W.; Stagg, Camille L. (Estuaries and Coasts, 2013)

The Federal Policy On Wetland Conservation - Environment Canada (1991)

North American Prairie Wetlands Are Important Non-forested Land-based Carbon Storage Sites - Euliss, N. H., Jr.; Gleason, R. A.; Olness, A.; McDougal, R. L.; Murkin, H. R.; Robarts, R. D.; Bourbonniere, R. A.; Warner, B. G. (Science of the Total Environment, 2006)
Keywords: Agriculture Canada Carbon/*analysis Conservation of Natural Resources Soil/analysis United States

The Wetland Continuum: a Conceptual Framework For Interpreting Biological Studies - Euliss, Ned H.; LaBaugh, James W.; Fredrickson, Leigh H.; Mushet, David M.; Laubhan, Murray K.; Swanson, George A.; Winter, Thomas C.; Rosenberry, Donald O.; Nelson, Richard D. (Wetlands, 2004)

Classification of Wetlands and DeepWater Habitats of the United States - Federal Geographic Data Committee (2013)

Canadian Biodiversity: Ecosystem Status and Trends 2010 - Federal Provincial and Territorial Governments of Canada (2010)

Drought-induced Carbon Loss in Peatlands - Fenner, N.; Freeman, C. (Nature Geoscience, 2011)
Keywords: phenol oxidase activity dissolved organic-carbon summer drought decomposition peat soil respiration variability diversity gradient

Fluxes of CO2, CH4 and N2O from a Welsh peatland following simulation of water table draw-down: Potential feedback to climatic change - Freeman, C.; Lock, M. A.; Reynolds, B. (Biogeochemistry, 1993)

The Fall and Rise of Wetlands of California's Great Central Valley - Garone, P. (Univ. of Calif. Press, 2011)

Ecosystem Services Derived From Wetland Conservation Practices in the United States Prairie Pothole Region With an Emphasis On the United States Department of Agriculture Conservation Reserve and Wetlands Reserve Programs - Gleason, R.; Laubhan, M.; Euliss, N., Jr. (U.S. Geological Survey Professional Paper 1745, 2008)

Greenhouse Gas Flux From Cropland and Restored Wetlands in the Prairie Pothole Region - Gleason, Robert A.; Tangen, Brian A.; Browne, Bryant A.; Euliss Jr, Ned H. (Soil Biology and Biochemistry, 2009)

Atmospheric Inverse Modeling To Constrain Regional-scale CO2 Budgets At High Spatial and Temporal Resolution - Gockede, M.; Michalak, A. M.; Vickers, D.; Turner, D. P.; Law, B. E. (Journal of Geophysical Research: Atmospheres, 2010)
Keywords: 4-dimensional data assimilation net ecosystem production old-growth forest carbon-dioxide ponderosa pine boundary-layer transport models united-states water-vapor flux

Hydrogeochemistry of Prairie Pothole Region Wetlands: Role of Long-term Critical Zone Processes - Goldhaber, Martin B.; Mills, Christopher T.; Morrison, Jean M.; Stricker, Craig A.; Mushet, David M.; LaBaugh, James W. (Chemical Geology, 2014)

Carbon budget of oligotrophic mire sites in the Southern Taiga of Western Siberia - Golovatskaya, Eugenia A.; Dyukarev, Egor A. (Plant and Soil, 2008)

Northern Peatlands - Role in the carbon-cycle and probabable responses to climatic warming - Gorham, E. (Ecological Applications, 1991)

Long-term carbon sequestration in North American peatlands - Gorham, Eville; Lehman, Clarence; Dyke, Arthur; Clymo, Dicky; Janssens, Joannes (Quaternary Science Reviews, 2012)

A Mesocosm Study of the Role of the Sedge Eriophorum Angustifolium in the Efflux of Methane-including That Due To Episodic Ebullition-from Peatlands - Green, S. M.; Baird, A. J. (Plant and Soil, 2012)
Keywords: peatlands methane flux ebullition vascular plants eriophorum angustifolium vascular plants carbon turnover ch4 emission wetlands peat transport water flux gas co2

Intermediate-scale Community-level Flux of CO2 and CH4 in a Minnesota Peatland: Putting the SPRUCE Project in a Global Context - Hanson, P. J.; Gill, A. L.; Xu, X.; Phillips, J. R.; Weston, D. J.; Kolka, R. K.; Riggs, J. S.; Hook, L. A. (Biogeochemistry, 2016)
Keywords: carbon budget carbon dioxide methane peat picea sphagnum methane emissions northern peatland biogeochemistry model carbon accumulation terrestrial ecosystems retrospective analysis ombrotrophic peatland european peatlands climate-change blanket bog

Attaining Whole-ecosystem Warming Using Air and Deep-soil Heating Methods With an Elevated CO2 Atmosphere - Hanson, P. J.; Riggs, J. S.; Nettles, W. R.; Phillips, J. R.; Krassovski, M. B.; Hook, L. A.; Gu, L. H.; Richardson, A. D.; Aubrecht, D. M.; Ricciuto, D. M.; Warren, J. M.; Barbier, C. (Biogeosciences, 2017)
Keywords: climate-change vegetation models carbon balance boreal forest flux temperature responses canopy practicality phenology

The influence of methane oxidation on the stable isotopic composition of methane emitted from Florida swamp forests - Happell, James D.; Chanton, Jeffrey P.; Showers, William S. (Geochimica et Cosmochimica Acta, 1994)

Methane flux from northern peatlands - Harriss, Robert C.; Gorham, Eville; Sebacher, Daniel I.; Bartlett, Karen B.; Flebbe, Patricia A. (Nature, 1985)

Methane Flux in Forested Freshwater Swamps of the Southeastern United States - Harriss, Robert C.; Sebacher, Daniel I. (Geophysical Research Letters, 1981)

Sources of Atmospheric Methane in the South Florida Environment - Harriss, Robert C.; Sebacher, Daniel I.; Bartlett, Karen B.; Bartlett, David S.; Crill, Patrick M. (Global Biogeochemical Cycles, 1988)

Methane Flux in the Great Dismal Swamp - Harriss, Robert C.; Sebacher, Daniel I.; Day, Frank P. (Nature, 1982)

Terrestrial carbon modeling: Baselines and projections in lowland ecosystems of Alaska - He, Y.; H. Genet; A.D. McGuire; Q. Zhuang; B. K. Wylie; Zhang, Y. (Baseline and Projected Future Carbon Storage and Greenhouse-Gas Fluxes in Ecosystems of Alaska: U.S. Geological Survey Professional Paper 1826, 2016)

Interpreting the variations in atmospheric methane fluxes observed above a restored wetland - Herbst, Mathias; Friborg, Thomas; Ringgaard, Rasmus; Soegaard, Henrik (Agricultural and Forest Meteorology, 2011)

Large contribution to inland water CO2 and CH4 emissions from very small ponds - Holgerson, Meredith A.; Raymond, Peter A. (Nature Geoscience, 2016)

Ecosystem Level Methane Fluxes From Tidal Freshwater and Brackish Marshes of the Mississippi River Delta: Implications For Coastal Wetland Carbon Projects - Holm, Guerry O.; Perez, Brian C.; McWhorter, David E.; Krauss, Ken W.; Johnson, Darren J.; Raynie, Richard C.; Killebrew, Charles J. (Wetlands, 2016)

A Review of the Export of Carbon in River Water: Fluxes and Processes - Hope, D.; Billett, M. F.; Cresser, M. S. (Environmental Pollution, 1994)

Marshland conversion to cropland in northeast China from 1950 to 2000 reduced the greenhouse effect - Huang, Y. A. O.; Sun, Wenjuan; Zhang, W. E. N.; Yu, Yongqiang; Su, Yanhua; Song, Changchun (Global Change Biology, 2010)
Keywords: cropland global warming potential greenhouse gas northeast China soil organic carbon wetland conversion

The Likely Impact of Elevated [CO2], Nitrogen Deposition, Increased Temperature and Management On Carbon Sequestration in Temperate and Boreal Forest Ecosystems: a Literature Review - Hyvonen, R.; Agren, G. I.; Linder, S.; Persson, T.; Cotrufo, M. F.; Ekblad, A.; Freeman, M.; Grelle, A.; Janssens, I. A.; Jarvis, P. G.; Kellomaki, S.; Lindroth, A.; et al. (New Phytologist, 2007)
Keywords: Carbon/*metabolism Carbon Dioxide/*metabolism *Ecosystem Nitrogen/*metabolism *Temperature Trees/*physiology

Greenhouse Gas Mitigation Options and Costs For Agricultural Land and Animal Production Within the United States - ICF International (2013)

Humedales Potenciales - Instituto Nacional de Estadística y Geografía (2010)

Supplement To the 2006 IPCC Guidelines For National Greenhouse Gas Inventories: Wetlands - IPCC (IPCC, 2013)

High Sensitivity of Peat Decomposition To climate Change Through Water-table Feedback - Ise, Takeshi; Dunn, Allison L.; Wofsy, Steven C.; Moorcroft, Paul R. (Nature Geoscience, 2008)

World Reference Base For Soil Resources 2006 - IUSS Working Group WRB (World Soil Resources Reports No. 103, 2006)

Carbon dioxide exchange rates from short- and long-hydroperiod Everglades freshwater marsh - Jimenez, K. L.; Starr, G.; Staudhammer, C. L.; Schedlbauer, J. L.; Loescher, H. W.; Malone, S. L.; Oberbauer, S. F. (Journal of Geophysical Research: Biogeosciences, 2012)
Keywords: CO2 fluxes Everglades National Park ecosystem respiration (Reco) freshwater marshes hydroperiod net ecosystem exchange (NEE) 0315 Biosphere/atmosphere interactions 0414 Biogeochemical cycles, processes, and modeling 0428 Carbon cycling 0439 Ecosystems, structure and dynamics 0476 Plant ecology

Wise Use of Mires and Peatlands - Background and Principles including a Framework for Decision-Making - Joosten, H.; Clarke, D. (International Mire Conservation Group and the International Peat Society. Saarijärvi, Finland, 2002)

Effects of spring flood and water level draw-down on methane dynamics in the littoral zone of boreal lakes - Juutinen; Alm; Martikainen; Silvola (Freshwater Biology, 2001)
Keywords: boreal lake marsh flooding littoral zone methane

Recent changes in the fire regime across the North American boreal region—Spatial and temporal patterns of burning across Canada and Alaska - Kasischke, Eric S.; Turetsky, Merritt R. (Geophysical Research Letters, 2006)
Keywords: 0429 Climate dynamics 0426 Biosphere/atmosphere interactions 0468 Natural hazards

Methane Dynamics Across a Tidally Flooded Riverbank Margin - Kelley, Cheryl A.; Martens, Christopher S.; Ussler, William (Limnology and Oceanography, 1995)

Seasonal variation in methane emission from a temperate Phragmites-dominated marsh: effect of growth stage and plant-mediated transport - Kim, JooN; Verma, Shashi B.; Billesbach, David P. (Global Change Biology, 1999)
Keywords: eddy covariance methane flux prairie wetland

The Role of the Wetland Reserve Program in Conservation Efforts in the Mississippi River Alluvial Valley - King, Sammy L.; Twedt, Daniel J.; Wilson, R. Randy (Wildlife Society Bulletin (1973-2006), 2006)

Three decades of global methane sources and sinks - Kirschke, Stefanie; Bousquet, Philippe; Ciais, Philippe; Saunois, Marielle; Canadell, Josep G.; Dlugokencky, Edward J.; Bergamaschi, Peter; Bergmann, Daniel; Blake, Donald R.; Bruhwiler, Lori; Cameron-Smith, Philip; Castaldi, Simona; et al. (Nature Geoscience, 2013)

Histosols - Kolka, R. K.; Rabenhorst, M. C.; Swanson, D. (Handbook of Soil Sciences Properties and Processes, 2011)

Isotope Analysis of Pyrolysis Products From Sphagnum Peat and Dissolved Organic Matter From Bog Water - Kracht, Oliver; Gleixner, Gerd (Organic Geochemistry, 2000)

Component greenhouse gas fluxes and radiative balance from two deltaic marshes in Louisiana: Pairing chamber techniques and eddy covariance - Krauss, Ken W.; Holm, Guerry O.; Perez, Brian C.; McWhorter, David E.; Cormier, Nicole; Moss, Rebecca F.; Johnson, Darren J.; Neubauer, Scott C.; Raynie, Richard C. (Journal of Geophysical Research: Biogeosciences, 2016)
Keywords: carbon fluxes wetlands soil fluxes net ecosystem exchange 0497 Wetlands 0428 Carbon cycling

Soil Greenhouse Gas Fluxes During Wetland Forest Retreat Along the Lower Savannah River, Georgia (USA) - Krauss, Ken W.; Whitbeck, Julie L. (Wetlands, 2012)

Organic Soils of Canada: Part 1. Wetland Organic soils - Kroetsch, David J.; Geng, Xiaoyuan; Chang, Scott X.; Saurette, Daniel D. (Canadian Journal of Soil Science, 2011)

Evaluacion Cuantitativa De La Pérdida De Humedales En Mexico - Landgrave, Rosario; Moreno-Casasola, Patricia (Investigación Ambiental, 2012)

CH4 production via CO2 reduction in a temperate bog: A source of 13C-depIeted CH4 - Lansdown, J. M.; Quay, P. D.; King, S. L. (Geochimica et Cosmochimica Acta, 1992)

Development and Validation of a Global Database of Lakes, Reservoirs and Wetlands - Lehner, Bernhard; Döll, Petra (Journal of Hydrology, 2004)

Methane emissions from created and restored freshwater and brackish marshes in southwest Florida, USA - Li, Xiaoyu; Mitsch, William J. (Ecological Engineering, 2016)

Methane Mitigation in Flooded Louisiana Rice Fields - Lindau, C. W.; Bollich, P. K.; Delaune, R. D.; Mosier, A. R.; Bronson, K. F. (Biology and Fertility of Soils, 1993)
Keywords: methane emissions flooded soil greenhouse gas wetland rice mitigation emission paddy fertilizer

Contrasting ecosystem CO2 fluxes of inland and coastal wetlands: a meta-analysis of eddy covariance data - Lu, Weizhi; Xiao, Jingfeng; Liu, Fang; Zhang, Yue; Liu, Chang'an; Lin, Guanghui (Global Change Biology, 2017)
Keywords: carbon budget cross-site synthesis ecosystem respiration gross primary productivity mangroves marshes net ecosystem productivity

Organic Matter Accumulation in a Restored Peatland: Evaluating Restoration Success - Lucchese, M.; Waddington, J. M.; Poulin, M.; Pouliot, R.; Rochefort, L.; Strack, M. (Ecological Engineering, 2010)
Keywords: peat land sphagnum organic matter rehabilitation npp gis ecohydrology abandoned cutover bog co2 exchange eastern canada sphagnum growth quebec decomposition regeneration limits water

Factors Causing Temporal and Spatial Variation in Heterotrophic and Rhizospheric Components of Soil Respiration in Afforested Organic Soil Croplands in Finland - Makiranta, P.; Minkkinen, K.; Hytonen, J.; Laine, J. (Soil Biology and Biochemistry, 2008)
Keywords: heterotrophic respiration rhizospheric respiration soil respiration afforestation organic soil mixed hardwood forest water-table levels litter decomposition southern finland co2 efflux terrestrial ecosystems agricultural soils root respiration carbon-dioxide temperature

Organic carbon and nitrogen concentrations and annual organic carbon load of six selected rivers of the United States - Malcolm, R. L.; Durum, W. H. (Water Supply Paper, 1976)

El Nino Southern Oscillation (ENSO) enhances CO2 exchange rates in freshwater Marsh ecosystems in the Florida everglades - Malone, S. L.; Staudhammer, C. L.; Oberbauer, S. F.; Olivas, P.; Ryan, M. G.; Schedlbauer, J. L.; Loescher, H. W.; Starr, G. (PLoS One, 2014)
Keywords: Carbon Dioxide/*analysis *Climatic Processes Florida Fresh Water/chemistry Hydrology *Wetlands

Decadal and Long-term Boreal Soil Carbon and Nitrogen Sequestration Rates Across a Variety of Ecosystems - Manies, K. l.; Harden, J. W.; Fuller, C. C.; Turetsky, M. R. (Biogeosciences, 2016)

Effects of Climate Change On Peatlands in the Far North of Ontario, Canada: a Synthesis - McLaughlin, Jim; Webster, Kara (Arctic, Antarctic, and Alpine Research, 2014)

Present State of Global Wetland Extent and Wetland Methane Modelling: Conclusions From a Model Inter-comparison Project (WETCHIMP) - Melton, J. R.; Wania, R.; Hodson, E. L.; Poulter, B.; Ringeval, B.; Spahni, R.; Bohn, T.; Avis, C. A.; Beerling, D. J.; Chen, G.; Eliseev, A. V.; Denisov, S. N.; et al. (Biogeosciences, 2013)

Seasonal Patterns and Controls On Methane and Carbon Dioxide Fluxes in Forested Swamp Pools - Miller, Daniel N.; Ghiors, William C. (Geomicrobiology Journal, 1999)

Climate Impacts To Peatland Forestry - Minkkinen, K.; Byrne, K.; Trettin, C. C. (Peatlands and Climate Change, 2008)

Wetlands. 5th Edition - Mitsch, WJ; Gosselink, JG (Wiley, 2015)

Landscape and Climate Change Threats To Wetlands of North and Central America - Mitsch, W. J.; Hernandez, M. E. (Aquatic Sciences, 2013)
Keywords: wetlands and climate change north american wetlands central american wetlands wetland status wetland threats fresh-water wetlands costa-rica nutrient accumulation mississippi delta mexico carbon restoration management methane

Wetlands and global change - Mitsch, W.J.; Wu, X. (Advances in Soil Science, Soil Management and Greenhouse Effect, 1995)

Methane emissions from Canadian peatlands - Moore, T. R.; Roulet., N. T. (Soils and Global Change, 1995)

Structural and Functional Loss in Restored Wetland Ecosystems - Moreno-Mateos, D.; Power, M. E.; Comin, F. A.; Yockteng, R. (PLoS Biology, 2012)
Keywords: Animals Australia Biodiversity Carbon/chemistry China Climate Conservation of Natural Resources/*trends Databases, Bibliographic Environmental Restoration and Remediation/methods/*trends Europe North America Plants Soil/chemistry Tidal Waves Vertebrates Water Cycle *Wetlands

Greenhouse gas fluxes in southeastern U.S. coastal plain wetlands under contrasting land uses - Morse, Jennifer L.; Ardón, Marcelo; Bernhardt, Emily S. (Ecological Applications, 2012)
Keywords: carbon dioxide denitrification greenhouse gas methane nitrous oxide North Carolina coastal plain restoration soil respiration wetland

Organic-Carbon Flow in a Swamp-Stream Ecosystem - Mulholland, P. J. (Ecological Monographs, 1981)

Transport of organic carbon to the oceans by rivers of North America: a synthesis of existing data - Mulholland, Patrick J.; Watts, Julia A. (Tellus, 1982)

Carbon Storage in US Wetlands - Nahlik, A. M.; Fennessy, M. S. (Nature Communications, 2016)

Methane Emissions From Created Riverine Wetlands - Nahlik, Amanda M.; Mitsch, William J. (Wetlands, 2010)

Beaver Population Fluctuations and Tropospheric Methane Emissions in Boreal Wetlands - Naiman, Robert J.; Manning, Thomas; Johnston, Carol A. (Biogeochemistry, 1991)

Carbon cycling in a tidal freshwater marsh ecosystem: a carbon gas flux study - Neubauer, Scott C.; Miller, W. David; Anderson, Iris Cofman (Marine Ecology Progress Series, 2000)

Spatial and Temporal Variation in Wet Area of Wetlands in the Prairie Pothole Region of North Dakota and South Dakota - Niemuth, Neal D.; Wangler, Brian; Reynolds, Ronald E. (Wetlands, 2010)

Contemporary Deposition and Long-Term Accumulation of Sediment and Nutrients By Tidal Freshwater Forested Wetlands Impacted By Sea Level Rise - Noe, Gregory B.; Hupp, Cliff R.; Bernhardt, Christopher E.; Krauss, Ken W. (Estuaries and Coasts, 2016)

North American Waterfowl Management Plan 2012: People Conserving Waterfowl and Wetlands - North American Waterfowl Management Plan Committee (2012)

Emissions of CH4, N2O and CO2 from a virgin fen and a fen drained for grassland in Finland - Nykanen, H.; Alm, J.; Lang, K.; Silvola, J.; Martikainen, P. J. (Journal of Biogeography, 1995)
Greenhouse gas fluxes (CH4, N2O and CO2) at a managed Finnish peat soil site were compared with those in a virgin fen in 1991 and 1992. The field site was drained about 60 years ago, and as it was used for pasturing and fodder production, the CH4 released by the cattle was estimated on the basis of data in the literature. The annual budgets of the gases were estimated and their GWP values calculated to assess the climatic impact of the current agricultural activity. Methane emission from the field site, 1 kg CH4-C ha(-1) yr(-1) was low, compared with that from the natural fen site, 260 kg CH4-C ha(-1) yr(-1). Annual N2O emission at the field site was 8 and 9 kg N2O-N ha(-1) yr(-1) in 1991 and 1992, respectively. Summer N2O emission in 1992 from vegetationless soil was five times higher than that from actual grassland. The N2O emissions from the natural fen site were low, close to the detection limit. The GWP for the field CH4 release (including cattle) corresponded to 0.3 X 10(4) kg CO2 ha(-1). The GWP for the annual N2O production was 0.2-0.4 x 10(4) kg CO2 ha(-1), while the grassland soil released 2.2 x 10(4) kg CO2 ha(-1) yr(-1). In its virgin state the field site may have accumulated 600 kg CO2 ha(-1) yr(-1). Although there must be a compensating carbon input into the soil in the form of root litter and exudates, a considerable carbon loss occurred (1.5 x 10(4) kg ha(-1) yr(-1)). The total GWP associated with cultivation was estimated to be 2.6 x 10(4) kg CO2 ha(-1) yr(-1).
Tr055 Times Cited:207 Cited References Count:40
Keywords: methane nitrous oxide carbon dioxide mire peat soil agriculture temperate forest soils nitrous-oxide fluxes water-table northern peatlands climatic-change carbon-dioxide methane uptake atmosphere denitrification fertilization

Quantifying Greenhouse Gas Sources and Sinks in Managed Wetland Systems - Ogle, S. M.; Hunt, P.; Trettin, C. (Quantifying Greenhouse Gas Fluxes in Agriculture and Forestry: Methods for Entity-Scale Inventory. Technical Bulletin Number 1939, 2014)

Environmental and physical controls on northern terrestrial methane emissions across permafrost zones - Olefeldt, David; Turetsky, Merritt R.; Crill, Patrick M.; McGuire, A. David (Global Change Biology, 2013)
Keywords: Methane permafrost sedges static chambers tundra wetlands

Interannual, Seasonal, and Retrospective Analysis of the Methane and Carbon Dioxide Budgets of a Temperate Peatland - Olson, D. M.; Griffis, T. J.; Noormets, A.; Kolka, R.; Chen, J. (Journal of Geophysical Research: Biogeosciences, 2013)
Keywords: high temporal resolution ecosystem co2 exchange sub-arctic fen northern peatland climate-change minnesota peatlands ombrotrophic bog eddy-correlation boreal peatland ch4 emissions

Landscape controls on N2O and CH4 emissions from freshwater mineral soil wetlands of the Canadian Prairie Pothole region - Pennock, Dan; Yates, Thomas; Bedard-Haughn, Angela; Phipps, Kim; Farrell, Richard; McDougal, Rhonda (Geoderma, 2010)

The Uncertain Climate Footprint of Wetlands Under Human Pressure - Petrescu, A. M.; Lohila, A.; Tuovinen, J. P.; Baldocchi, D. D.; Desai, A. R.; Roulet, N. T.; Vesala, T.; Dolman, A. J.; Oechel, W. C.; Marcolla, B.; Friborg, T.; Rinne, J.; et al. (Proceedings of the National Academy of Sciences USA, 2015)
Keywords: Carbon Dioxide/metabolism *Climate *Climate Change Ecology/methods *Ecosystem Geography Human Activities Humans Methane/metabolism Models, Theoretical Nitrous Oxide/metabolism Plants/classification/metabolism Temperature Uncertainty *Wetlands carbon dioxide methane radiative forcing wetland conversion

Effects of Water Table Position and Plant Functional Group On Plant Community, Aboveground Production, and Peat Properties in a Peatland Mesocosm Experiment (PEATcosm) - Potvin, L. R.; Kane, E. S.; Chimner, R. A.; Kolka, R. K.; Lilleskov, E. A. (Plant and Soil, 2015)
Keywords: peatland plant functional group water table sphagnum ericaceae sedge climate-change boreal peatlands sphagnum mosses level drawdown co2 exchange organic-matter pine mires bog growth vegetation

Carbon-Dioxide and Methane Exports From a Southeastern Floodplain Swamp - Pulliam, W. M. (Ecological Monographs, 1993)
Keywords: anaerobic biogeochemistry blackwater carbon floodplains georgia USA methane methanogenesis ogeechee river respiration roots wetlands sulfate reduction blackwater river rice paddies organic-matter eutrophic lake united-states forest floor flux oxidation water

Factors influencing methane flux from a boreal forest wetland in Saskatchewan, Canada - Rask, Holly; Schoenau, Jeff; Anderson, Darwin (Soil Biology and Biochemistry, 2002)

Event controlled DOC export from forested watersheds - Raymond, Peter A.; Saiers, James E. (Biogeochemistry, 2010)

Quantifying Soil Carbon Loss and Uncertainty From a Peatland Wildfire Using Multi-temporal LiDAR - Reddy, A. D.; Hawbaker, T. J.; Wurster, F.; Zhu, Z.; Ward, S.; Newcomb, D.; Murray, R. (Remote Sensing of Environment, 2015)
Keywords: soil carbon fire peat lands lidar vertical accuracy drainage rates emissions indonesia responses finland limits mires pool

Greenhouse Gas Fluxes From Restored Agricultural Wetlands and Natural Wetlands, Northwestern Indiana - Richards, Brianna; Craft, Christopher B. (The Role of Natural and Constructed Wetlands in Nutrient Cycling and Retention on the Landscape, 2015)

Impacts of Peatland Ditching and Draining On Water Quality and Carbon Sequestration Benefits of Peatland Restoration - Richardson, C. J.; Flanagan, N.; Wang, H.; Ho, M. (Eastern North Carolina/Southeastern Virginia Strategic Habitat Conservation Team, U.S. Fish and Wildlife Service, Region 4 and The Nature Conservancy North Carolina Chapter, 2014)

Peatlands, Carbon Storage, Greenhouse Gases, and the Kyoto Protocol: Prospects and Significance For Canada - Roulet, N. T. (Wetlands, 2000)
Keywords: peatlands greenhouse gases kyoto protocol land-use change continental western canada northern peatlands climatic-change hydroelectric reservoirs dioxide exchange boreal forests organic soils co2 fluxes methane

Greenhouse Gas Fluxes From Restored Agricultural Wetlands and Natural Wetlands, Northwestern Indiana - Richards, Brianna; Craft, Christopher B. (The Role of Natural and Constructed Wetlands in Nutrient Cycling and Retention on the Landscape, 2015)

The Global Methane Budget 2000–2012 - Saunois, Marielle; Bousquet, Philippe; Poulter, Ben; Peregon, Anna; Ciais, Philippe; Canadell, Josep G.; Dlugokencky, Edward J.; Etiope, Giuseppe; Bastviken, David; Houweling, Sander; Janssens-Maenhout, Greet; Tubiello, Francesco N.; et al. (Earth System Science Data, 2016)

Seasonal differences in the CO2 exchange of a short-hydroperiod Florida Everglades marsh - Schedlbauer, Jessica L.; Oberbauer, Steven F.; Starr, Gregory; Jimenez, Kristine L. (Agricultural and Forest Meteorology, 2010)

Source and Transformations of Lignin in Carex-dominated Peat - Schellekens, Judith; Buurman, Peter; Kuyper, Thomas W. (Soil Biology and Biochemistry, 2012)

Methane Production and Emissions from Four Reclaimed and Pristine Wetlands of Southeastern United States - Schipper, Louis; Reddy, Konda (1994)

Climate Change and the Permafrost Carbon Feedback - Schuur, E. A.; McGuire, A. D.; Schadel, C.; Grosse, G.; Harden, J. W.; Hayes, D. J.; Hugelius, G.; Koven, C. D.; Kuhry, P.; Lawrence, D. M.; Natali, S. M.; Olefeldt, D.; et al. (Nature, 2015)
Keywords: Arctic Regions *Carbon Cycle Carbon Dioxide/analysis *Climate Change Feedback Freezing Methane/analysis Permafrost/*chemistry Seawater/chemistry Uncertainty

Atmospheric methane sources: Alaskan tundra bogs, an alpine fen, and a subarctic boreal marsh - Sebacher, Daniel I.; Harriss, Robert C.; Bartlett, Karen B.; Sebacher, Shirley M.; Grice, Shirley S. (Tellus B: Chemical and Physical Meteorology, 1986)

Seasonal variations of methane fluxes from an unvegetated tidal freshwater mudflat (Hammersmith Creek, GA) - Segarra, K. E. A.; Samarkin, V.; King, E.; Meile, C.; Joye, S. B. (Biogeochemistry, 2013)

A three-year study of controls on methane emissions from two Michigan peatlands - Shannon, RobertD; White, JeffreyR (Biogeochemistry, 1994)

Development of Wetland Plant Communities - Sharitz, R. R.; Pennings, S. C. (Ecology of Freshwater and Estuarine Wetlands, 2006)

Micrometeorological Measurements of Methane Flux in a Minnesota Peatland during Two Growing Seasons - Shurpali, N. J.; Verma, S. B. (Biogeochemistry, 1998)

Tropical Wetlands: a Missing Link in the Global Carbon Cycle? - Sjogersten, S.; Black, C. R.; Evers, S.; Hoyos-Santillan, J.; Wright, E. L.; Turner, B. L. (Global Biogeochem Cycles, 2014)
Keywords: carbon dioxide decomposition methane net primary productivity tropical wetland

Organic matter chemistry controls greenhouse gas emissions from permafrost peatlands - Sjögersten, S.; Caul, S.; Daniell, T. J.; Jurd, A. P. S.; O'Sullivan, O. S.; Stapleton, C. S.; Titman, J. J. (Soil Biology and Biochemistry, 2016)

Heritage Values and Functions of Wetlands in Southern Mexico - Smardon, R. C. (Landscape and Urban Planning, 2006)
Keywords: wetland heritage wetland archeology consumptive and non-consumptive uses resource conflict raised-field agriculture lowland maya archaeology tlaxcala

Seasonality of methane emissions from five lakes and associated wetlands of the Colorado Rockies - Smith, Lesley K.; Lewis, William M. (Global Biogeochemical Cycles, 1992)
Keywords: 0315 Biosphere/atmosphere interactions 1806 Chemistry of fresh water 1845 Limnology

Key To Soil Taxonomy - Soil Survey Staff (2010)

Fluxes of carbon dioxide and methane from swamp and impact factors in Sanjiang Plain, China - Song, Changchun; Yan, Baixing; Wang, Yuesi; Wang, Yiyong; Lou, Yanjing; Zhao, Zhichun (Chinese Science Bulletin, 2003)

Restoring Bottomland Hardwood Ecosystems in the Lower Mississippi Alluvial Valley - Stanturf, J. A.; Gardiner, E. S.; Hamel, P. B.; Devall, M. S.; Leininger, T. D.; Warren, M. E. (Journal of Forestry, 2000)
Keywords: reforestation forest

Unintended Impacts of Public Investments On Private Decisions: the Depletion of Forested Wetlands - Stavins, Robert N.; Jaffe, Adam B. (American Economic Review, 1990)

An Inventory-based Analysis of Canada's Managed Forest Carbon Dynamics, 1990 To 2008 - Stinson, G.; Kurz, W. A.; Smyth, C. E.; Neilson, E. T.; Dymond, C. C.; Metsaranta, J. M.; Boisvenue, C.; Rampley, G. J.; Li, Q.; White, T. M.; Blain, D. (Global Change Biology, 2011)

Carbon dioxide and methane exchange at a cool-temperate freshwater marsh - Strachan, Ian B.; Nugent, Kelly A.; Crombie, Stephanie; Bonneville, Marie-Claude (Environmental Research Letters, 2015)

Response of peatland carbon dioxide and methane fluxes to a water table drawdown experiment - Strack, M.; Waddington, J. M. (Global Biogeochemical Cycles, 2007)
Keywords: climate change peatland carbon cycling water table drawdown 0428 Carbon cycling 0497 Wetlands 0490 Trace gases 1813 Eco-hydrology

Effect of water table drawdown on northern peatland methane dynamics: Implications for climate change - Strack, M.; Waddington, J. M.; Tuittila, E. S. (Global Biogeochemical Cycles, 2004)
Keywords: climate change methane peatland 0315 Biosphere/atmosphere interactions 1615 Biogeochemical cycles, processes, and modeling 1851 Plant ecology 1890 Wetlands

Impact of Hydrological Variations On Modeling of Peatland CO2 Fluxes: Results From the North American Carbon Program Site Synthesis - Sulman, Benjamin N.; Desai, Ankur R.; Schroeder, Nicole M.; Ricciuto, Dan; Barr, Alan; Richardson, Andrew D.; Flanagan, Lawrence B.; Lafleur, Peter M.; Tian, Hanqin; Chen, Guangsheng; Grant, Robert F.; Poulter, Benjamin; et al. (Journal of Geophysical Research: Biogeosciences, 2012)

In situ Methane Production from Acid Peat in Plant Communities with Different Moisture Regimes in a Subarctic Mire - Svensson, Bo H.; Rosswall, Thomas (Oikos, 1984)

Effects of Land Use On Greenhouse Gas Fluxes and Soil Properties of Wetland Catchments in the Prairie Pothole Region of North America - Tangen, B. A.; Finocchiaro, R. G.; Gleason, R. A. (Science of the Total Environment, 2015)
Keywords: Agricultural drainage Carbon sequestration Methane Nitrous oxide Water-filled pore space Wetland restoration

The Effect of Climate Change On Carbon in Canadian Peatlands - Tarnocai, C. (Global and Planetary Change, 2006)
Keywords: peatlands arctic boreal canada climate change

Peatlands of Canada - Tarnocai, C.; Kettles, I. M.; Lacelle, B. P. (2005)

Accumulation Rates of Carbon in Mires in Finland and Implications For Climate Change - Tolonen, K.; Turunen, J. (The Holocene, 1996)

Recovery of Carbon and Nutrient Pools in a Northern Forested Wetland 11 Years After Harvesting and Site Preparation - Trettin, C. C.; Jurgensen, M. F.; Gale, M. R.; McLaughlin, J. W. (Forest Ecology and Management, 2011)
Keywords: forested wetland carbon balance harvest and site preparation impacts histic mineral soil wetland mineral substrate organic-carbon nitrogen biomass biogeochemistry availability equations responses dynamics peatland

Influence of Climate Change Factors On Carbon Dynamics in Northern Forested Peatlands - Trettin, C. C.; Laiho, R.; Minkkinen, K.; Laine, J. (Canadian Journal of Soil Science, 2006)
Keywords: peatland carbon cycle methane forest wetland water-level drawdown drained pine mires long-term litter decomposition methane emissions boreal peatlands moisture conditions accumulation rates vascular plants organic-matter

Experimental Drying Intensifies Burning and Carbon Losses in a Northern Peatland - Turetsky, M. R.; Donahue, W. F.; Benscoter, B. W. (Nature Communications, 2011)
Keywords: Carbon/*analysis Ecosystem *Fires Soil/*analysis

Recent acceleration of biomass burning and carbon losses in Alaskan forests and peatlands - Turetsky, Merritt R.; Kane, Evan S.; Harden, Jennifer W.; Ottmar, Roger D.; Manies, Kristen L.; Hoy, Elizabeth; Kasischke, Eric S. (Nature Geoscience, 2011)

A Synthesis of Methane Emissions From 71 Northern, Temperate, and Subtropical Wetlands - Turetsky, M. R.; Kotowska, A.; Bubier, J.; Dise, N. B.; Crill, P.; Hornibrook, E. R.; Minkkinen, K.; Moore, T. R.; Myers-Smith, I. H.; Nykanen, H.; Olefeldt, D.; Rinne, J.; et al. (Global Change Biology, 2014)
Keywords: Environment Geography Groundwater/*analysis Methane/analysis/*metabolism Soil/*chemistry Temperature *Wetlands bog carbon disturbance fen graminoids peat swamp vegetation water table

The disappearance of relict permafrost in boreal north America: Effects on peatland carbon storage and fluxes - Turetsky, M. R.; Wieder, R. K.; Vitt, D. H.; Evans, R. J.; Scott, K. D. (Global Change Biology, 2007)
Keywords: boreal carbon CH4 climate change CO2 degradation litter quality peat peatlands permafrost

Count It By Acre Or Function-mitigation Adds Up To Net Loss of Wetlands - Turner, R. Eugene; Redmond, Ann M.; Zedler, Joy B. (National Wetlands Newsletter, 2001)

Response of CO2 and CH4 emissions from Peatlands to Warming and Water Table Manipulation - Updegraff, Karen; Bridgham, Scott D.; Pastor, John; Weishampel, Peter; Harth, Calvin (Ecological Applications, 2001)

Compensatory Mitigation For Losses of Aquatic Resources - USACE (2008)

ACEP ―Agricultural Conservation Easement Program: Natural Resource Conservation Service - USDA (U.S. Department of Agriculture, 2014)

Forest Inventory and Analysis - USDA Forest Service

Status and Trends of Wetlands in the Conterminous United States 2004 To 2009, Report To Congress - USFWS (2011)

The Impact of Peat Harvesting and Natural Regeneration On the Water Balance of an Abandoned Cutover Bog, Quebec - Van Seters, Tim E.; Price, Jonathan S. (Hydrological Processes, 2001)

Contribution of different wetland plant species to the DOC exported from a mesocosm experiment in the Florida Everglades - Villa, Jorge A.; Mitsch, William J.; Song, Keunyea; Miao, ShiLi (Ecological Engineering, 2014)

Northern Canadian Wetlands: Net Ecosystem CO2 Exchange and Climatic Change - Waddington, J. M.; Griffis, T. J.; Rouse, W. R. (Climatic Change, 1998)

Hydrological Feedbacks in Northern Peatlands - Waddington, J. M.; Morris, P. J.; Kettridge, N.; Granath, G.; Thompson, D. K.; Moore, P. A. (Ecohydrology, 2015)

Examining the Utility of the Canadian Forest Fire Weather Index System in Boreal Peatlands - Waddington, J. M.; Thompson, D. K.; Wotton, M.; Quinton, W. L.; Flannigan, M. D.; Benscoter, B. W.; Baisley, S. A.; Turetsky, M. R. (Canadian Journal of Forest Research, 2012)

Dual Controls On Carbon Loss During Drought in Peatlands - Wang, H. J.; Richardson, C. J.; Ho, M. C. (Nature Climate Change, 2015)
Keywords: phenol oxidase activity microbial community boreal peatlands organic-matter water-level peat soil decomposition feedback fluxes

Long-Term Consequences of Grazing and Burning on Northern Peatland Carbon Dynamics - Ward, Susan E.; Bardgett, Richard D.; McNamara, Niall P.; Adamson, John K.; Ostle, Nick J. (Ecosystems, 2007)

Regional-scale measurements of CH4 exchange from a tall tower over a mixed temperate/boreal lowland and wetland forest - Werner, Cindy; Davis, Kenneth; Bakwin, Peter; Yi, Chuixiang; Hurst, Dale; Lock, Loreen (Global Change Biology, 2003)

Landscape patterns of CH4 fluxes in an alpine tundra ecosystem - West, A. E.; Brooks, P. D.; Fisk, M. C.; Smith, L. K.; Holland, E. A.; Jaeger, Iii C. H.; Babcock, S.; Lai, R. S.; Schmidt, S. K. (Biogeochemistry, 1999)

Inland Wetland Mineral Soils - Wickland, K. P.; Krusche, A. V.; Kolka, R. K.; Kishimoto-Mo, A. W.; Chimner, R. A.; Serengil, Y.; Ogle, S.; Srivastava, N. (IPCC 2013 Supplement to the 2006 IPCC Guidelines for National Greenhouse Gas Inventories: Wetlands, 2014)

Methane flux in subalpine wetland and unsaturated soils in the southern Rocky Mountains - Wickland, Kimberly P.; Striegl, Robert G.; Schmidt, Steven K.; Mast, M. Alisa (Global Biogeochemical Cycles, 1999)
Keywords: 0315 Biosphere/atmosphere interactions 1615 Biogeochemical cycles, processes, and modeling 1890 Wetlands

Methane production and sulfate reduction in two Appalachian peatlands - Wieder, R. Kelma; Yavitt, JosephB; Lang, GeraldE (Biogeochemistry, 1990)

Seasonal Variation of Methane Emissions From a Temperate Swamp - Wilson, John O.; Crill, Patrick M.; Bartlett, Karen B.; Sebacher, Daniel I.; Harriss, Robert C.; Sass, Ronald L. (Biogeochemistry, 1989)

Hydrology of Prairie Pothole Wetlands During Drought and Deluge: a 17-year Study of the Cottonwood Lake Wetland Complex in North Dakota in the Perspective of Longer Term Measured and Proxy Hydrological Records - Winter, Thomas C.; Rosenberry, Donald O. (Climatic Change, 1998)

The Effects of Organic Matter Amendments On Greenhouse Gas Emissions From a Mitigation Wetland in Virginia’s Coastal Plain - Winton, R. Scott; Richardson, Curtis J. (Wetlands, 2015)

Surface methane emissions from different land use types during various water levels in three major drawdown areas of the Three Gorges Reservoir - Yang, Le; Lu, Fei; Wang, Xiaoke; Duan, Xiaonan; Song, Wenzhi; Sun, Binfeng; Chen, Shuai; Zhang, Qianqian; Hou, Peiqiang; Zheng, Feixiang; Zhang, Ye; Zhou, Xiaoping; et al. (Journal of Geophysical Research: Atmospheres, 2012)

Methane fluxes in wetland and forest soils, beaver ponds, and low-order streams of a temperate forest ecosystem - Yavitt, J. B.; Lang, G. E.; Sexstone, A. J. (Journal of Geophysical Research, 1990)

Methane fluxes in a northern hardwood forest ecosystem in relation to acid precipitation - Yavitt, J. B.; Simmons, J. A.; Fahey, T. J. (Chemosphere, 1993)

Production of methane and carbon dioxide in peatland ecosystems across North America: Effects of temperature, aeration, and organic chemistry of peat - Yavitt, Joseph B.; Williams, Christopher J.; Wieder, R. Kelman (Geomicrobiology Journal, 1997)

Effect of Hydrological Conditions On Nitrous Oxide, Methane, and Carbon Dioxide Dynamics in a Bottomland Hardwood Forest and Its Implication For Soil Carbon Sequestration - Yu, Kewei; Faulkner, Stephen P.; Baldwin, Michael J. (Global Change Biology, 2008)

A Method For Assessing Carbon Stocks, Carbon Sequestration, and Greenhouse-gas Fluxes in Ecosystems of the United States Under Present Conditions and Future Scenarios - Zhu, Z.; McGuire, A.D. (U.S. Geological Survey Scientific Investigations Report 2010-5233, 2010)

Baseline and Projected Future Carbon Storage and Greenhouse-gas Fluxes in the Great Plains Region of the United States - Zhu, Z.; McGuire, A.D. (U.S. Geological Survey Professional Paper 1787, 2011)

Baseline and Projected Future Carbon Storage and Greenhouse-gas Fluxes in Ecosystems of Alaska - Zhu, Z.; McGuire, A.D. (U.S. Geological Survey Professional Paper 1826, 2016)

Baseline and Projected Future Carbon Storage and Greenhouse-gas Fluxes in Ecosystems of the Western United States - Zhu, Z.; Reed, B. (U.S. Geological Survey Professional Paper 1797, 2012)

Baseline and Projected Future Carbon Storage and Greenhouse-gas Fluxes in Ecosystems of the Eastern United States - Zhu, Zhiliang; Reed, Bradley (U.S. Geological Survey Professional Paper 1804, 2014)

Canadian wetlands: Environmental gradients and classification - Zoltai, S. C.; Vitt, D. H. (Vegetatio, 1995)

Heterogeneity of light use efficiency in a northern Wisconsin forest: Implications for modeling net primary production with remote sensing - Ahl, D. E.; S. T. Gower; D. S. Mackay; S. N. Burrows; J. M. Norman; Diak, G. R. (Remote Sensing and the Environment, 2004)

Methane flux from the Florida Everglades: Patterns of variability in a regional wetland ecosystem - Bartlett, D. S.; K. B. Bartlett; J. M.Hartman; R. C. Hanks; D. C. Sebacher; R. Pelletier-Travis; Dow, D. D.; Brannon, D. P. (Global Biogeochemical Cycles, 1989)

Potential feedbacks of northern wetlands on climate change - Bridgham, S.D; Johnston, C.A.; Pastor, J.; Updegraff, K. (BioScience, 1995)

Carbon balance of a temperate poor fen - Carroll, P.; Crill, P. (Global Biogeochemical Cycles, 1997)
The dynamic carbon balance of a southeastern New Hampshire wetland was constructed for the 1994 growing season using a light-dark box sampling method. Net ecosystem exchange (NEE) (n=414) and ecosystem respiration (n=234) measurements were made at the 1.7 ha Sphagnum spp. dominated poor fen. The NEE rates ranged from -192 to 492 mg C m(-2) h(-1) and the ecosystem respiration measurements were between -10 and -365 mg C m(-2) h(-1). The negative values represent a loss of carbon from the wetland system. NEE and respiration data were used to derive photosynthesis rates of the vegetation at the study site. A simple model, using hourly averages of photosynthetically active radiation, and air and soil temperatures to generate hourly rates of photosynthesis and respiration, was constructed to interpolate the carbon cycling rates at this fen through the entire 1994 growing season. Results of the carbon balance model suggest that the wetland lost an estimated 145 g C m(-2) for the 9 month modeling period (April through December). The 1994 climate season was warmer (+1.15 degrees C/month) and drier (-12.3 cm) than the 30 year normals for Durham, New Hampshire, the nearest meteorological station. These data suggest that if future climate change brings about warmer temperatures and lower water tables in peatland soils, positive climatic feedback leading to substantial releases of CO2 from boreal and subarctic peatlands is probable.
Xt619 Times Cited:81 Cited References Count:34
Keywords: methane flux northern minnesota climatic-change arctic tundra CO2 exchange peatlands dioxide variability emissions dynamics

Influence of water table levels on CO2 emissions in a Colorado subalpine fen: an in situ microcosm study - Chimner, Rodney A.; Cooper, David J. (Soil Biology and Biochemistry, 2003)

Linking Belowground Carbon Allocation to Anaerobic CH4 and CO2 Production in a Forested Peatland, New York State - Coles, Janice R. P.; Yavitt, Joseph B. (Geomicrobiology Journal, 2004)

Climate control on temporal variability of methane flux from a poor fen in southeastern New Hampshire: Measurement and modeling - Frolking, S.; Crill, P. (Global Biogeochemical Cycles, 1994)

Carbon and sediment accumulation in the Everglades (USA) during the past 4000 years: Rates, drivers, and sources of error - Glaser, Paul H.; Volin, John C.; Givnish, Thomas J.; Hansen, Barbara C. S.; Stricker, Craig A. (Journal of Geophysical Research: Biogeosciences, 2012)

Warmer spring conditions increase annual methane emissions from a boreal peat landscape with sporadic permafrost - Helbig, Manuel; Quinton, William L.; Sonnentag, Oliver (Environmental Research Letters, 2017)

Ecosystem scale methane fluxes in a natural temperate bog-pine forest in southern Germany - Hommeltenberg, Janina; Mauder, Matthias; Drösler, Matthias; Heidbach, Katja; Werle, Peter; Schmid, Hans Peter (Agricultural and Forest Meteorology, 2014)

Carbon Storage and Fluxes within Freshwater Wetlands: a Critical Review - Kayranli, Birol; Scholz, Miklas; Mustafa, Atif; Hedmark, A. (Society of Wetland Scientists, 2009)

Agricultural peatland restoration: effects of land-use change on greenhouse gas (CO2 and CH4) fluxes in the Sacramento-San Joaquin Delta - Knox, S. H.; Sturtevant, C.; Matthes, J. H.; Koteen, L.; Verfaillie, J.; Baldocchi, D. (Global Change Biology, 2015)
Agricultural drainage of organic soils has resulted in vast soil subsidence and contributed to increased atmospheric carbon dioxide (CO2) concentrations. The Sacramento-San Joaquin Delta in California was drained over a century ago for agriculture and human settlement and has since experienced subsidence rates that are among the highest in the world. It is recognized that drained agriculture in the Delta is unsustainable in the long-term, and to help reverse subsidence and capture carbon (C) there is an interest in restoring drained agricultural land-use types to flooded conditions. However, flooding may increase methane (CH4) emissions. We conducted a full year of simultaneous eddy covariance measurements at two conventional drained agricultural peatlands (a pasture and a corn field) and three flooded land-use types (a rice paddy and two restored wetlands) to assess the impact of drained to flooded land-use change on CO2 and CH4 fluxes in the Delta. We found that the drained sites were net C and greenhouse gas (GHG) sources, releasing up to 341 g C m(-2) yr(-1) as CO2 and 11.4 g C m(-2) yr(-1) as CH4. Conversely, the restored wetlands were net sinks of atmospheric CO2, sequestering up to 397 g C m(-2) yr(-1). However, they were large sources of CH4, with emissions ranging from 39 to 53 g C m(-2) yr(-1). In terms of the full GHG budget, the restored wetlands could be either GHG sources or sinks. Although the rice paddy was a small atmospheric CO2 sink, when considering harvest and CH4 emissions, it acted as both a C and GHG source. Annual photosynthesis was similar between sites, but flooding at the restored sites inhibited ecosystem respiration, making them net CO2 sinks. This study suggests that converting drained agricultural peat soils to flooded land-use types can help reduce or reverse soil subsidence and reduce GHG emissions.
Knox, Sara Helen Sturtevant, Cove Matthes, Jaclyn Hatala Koteen, Laurie Verfaillie, Joseph Baldocchi, Dennis eng Research Support, Non-U.S. Gov't Research Support, U.S. Gov't, Non-P.H.S. England 2014/09/18 06:00 Glob Chang Biol. 2015 Feb;21(2):750-65. doi: 10.1111/gcb.12745. Epub 2014 Oct 31.
Keywords: *Agriculture Air Pollutants/*analysis California Carbon Cycle Carbon Dioxide/*analysis *Conservation of Natural Resources Environmental Monitoring Methane/*analysis Soil/*chemistry Wetlands carbon flux drained eddy covariance greenhouse gas balance land-use change methane peatland restored rice wetland

How strong is the current carbon sequestration of an Atlantic blanket bog? - Koehler, Ann-Kristin; Sottocornola, Matteo; Kiely, Gerard (Global Change Biology, 2011)

Evaluation of National Wetland Inventory maps in a heavily forested region in the upper Great Lakes - Kudray, G. M.; Gale, M. R. (Wetlands, 2000)
National Wetland Inventory (NWI) maps are widely used in the United States but have not been independently evaluated in the Great Lakes region nor in forested areas with level topography. Field data from 148 plots in the Hiawatha National Forest ecological classification and inventory program were combined with an additional review to evaluate NWI mapping accuracy. NWI maps were over 90% accurate in identifying uplands and jurisdictional wetlands. All nonforested wetlands were identified correctly. Uplands were correctly identified 96.9% of the time. The lowest level of accuracy, 90.7%, was achieved in identifying forested wetlands. The most common error was the NWI classification of wetlands on the AuGres soil series, a somewhat poorly drained upland soil that often occurs in complexes with wetland soils in the region. Forested wetlands with a cover type similar to adjacent uplands were also a source of error on NWI maps. The already high accuracy of NWI maps could be improved by the mapping of wetland-upland complexes, a development corresponding to the increased mapping of hydric-nonhydric soil complexes in area soil surveys. The continued refinement of regional lists of hydrophytic vegetation is supported by indicator status discrepancies between an extensive Hiawatha National Forest database and the current NWI list for the region.
386xg Times Cited:32 Cited References Count:23
Keywords: map accuracy maps national wetland inventory plant indicators soils

Nitrate shaped the selenate-reducing microbial community in a hydrogen-based biofilm reactor - Lai, C. Y.; Yang, X.; Tang, Y.; Rittmann, B. E.; Zhao, H. P. (Environmental Science Technology, 2014)
To study the effect of nitrate (NO3(-)) on selenate (SeO4(2-)) reduction, we tested a H2-based biofilm with a range of influent NO3(-) loadings. When SeO4(2-) was the only electron acceptor (stage 1), 40% of the influent SeO4(2-) was reduced to insoluble elemental selenium (Se(0)). SeO4(2-) reduction was dramatically inhibited when NO3(-) was added at a surface loading larger than 1.14 g of N m(-2) day(-1), when H2 delivery became limiting and only 80% of the input NO3(-) was reduced (stage 2). In stage 3, when NO3(-) was again removed from the influent, SeO4(2-) reduction was re-established and increased to 60% conversion to Se(0). SeO4(2-) reduction remained stable at 60% in stages 4 and 5, when the NO3(-) surface loading was re-introduced at </= 0.53 g of N m(-2) day(-1), allowing for complete NO3(-) reduction. The selenate-reducing microbial community was significantly reshaped by the high NO3(-) surface loading in stage 2, and it remained stable through stages 3-5. In particular, the abundance of alpha-Proteobacteria decreased from 30% in stage 1 to less than 10% of total bacteria in stage 2. beta-Proteobacteria, which represented about 55% of total bacteria in the biofilm in stage 1, increased to more than 90% of phylotypes in stage 2. Hydrogenophaga, an autotrophic denitrifier, was positively correlated with NO3(-) flux. Thus, introducing a NO3(-) loading high enough to cause H2 limitation and suppress SeO4(2-) reduction had a long-lasting effect on the microbial community structure, which was confirmed by principal coordinate analysis, although SeO4(2-) reduction remained intact.
Lai, Chun-Yu Yang, Xiaoe Tang, Youneng Rittmann, Bruce E Zhao, He-Ping eng Research Support, Non-U.S. Gov't 2014/03/04 06:00 Environ Sci Technol. 2014 Mar 18;48(6):3395-402. doi: 10.1021/es4053939. Epub 2014 Mar 7.
Keywords: *Biofilms Bioreactors/*microbiology Hydrogen/metabolism *Microbial Consortia Nitrates/*metabolism Proteobacteria/metabolism Selenic Acid/*metabolism

Spatial and temporal variations of methane flux measured by autochambers in a temperate ombrotrophic peatland - Lai, Derrick Y. F.; Moore, Tim R.; Roulet, Nigel T. (Journal of Geophysical Research: Biogeosciences, 2014)
AbstractWe measured CH4 flux at high temporal resolution with triplicate autochambers from three different plant communities at the ombrotrophic Mer Bleue bog in Canada to investigate the spatial and temporal variations, and factors that related to the CH4 flux. Our results show that seasonal mean CH4 fluxes from the Eriophorum-dominated community were 1.4–2.2 and 3.7–5.5 times higher than those from Maianthemum/Ledum and Chamaedaphne communities, respectively. Significant interannual variations in CH4 flux were observed in Maianthemum/Ledum and Chamaedaphne communities, attributable to a 55–60% reduction of mean summer (July–September) CH4 flux in 2010 as a consequence of a 5.5–9.0 cm lower mean summer water table compared to 2009. The Eriophorum community showed a much larger rate of increase in CH4 flux with peat temperature in the early growing season than in midsummer, which might be caused by a concomitant increase in root exudation of labile carbon for methanogenesis. Temporal variability of log-transformed CH4 flux was correlated (r ≥ 0.4) with peat temperature only when water table was less than 20, 30, and 40 cm below the peat surface for Maianthemum/Ledum, Chamaedaphne, and Eriophorum communities, respectively. This difference in water table threshold among communities might partly be related to differences in rooting depth and hence the ability of plants to sustain CH4 flux in dry conditions. These results suggest that modeling of CH4 flux from ombrotrophic peatlands over time should take into account the role of different vegetation types, since the relationships between CH4 emissions and environmental factors vary among vascular plant communities.

A database and synthesis of northern peatland soil properties and Holocene carbon and nitrogen accumulation - Loisel, Julie; Yu, Zicheng; Beilman, David W; Camill, Philip; Alm, Jukka; Amesbury, Matthew J; Anderson, David; Andersson, Sofia; Bochicchio, Christopher; Barber, Keith; Belyea, Lisa R; Bunbury, Joan; et al. (The Holocene, 2014)
Here, we present results from the most comprehensive compilation of Holocene peat soil properties with associated carbon and nitrogen accumulation rates for northern peatlands. Our database consists of 268 peat cores from 215 sites located north of 45°N. It encompasses regions within which peat carbon data have only recently become available, such as the West Siberia Lowlands, the Hudson Bay Lowlands, Kamchatka in Far East Russia, and the Tibetan Plateau. For all northern peatlands, carbon content in organic matter was estimated at 42 ± 3% (standard deviation) for Sphagnum peat, 51 ± 2% for non-Sphagnum peat, and at 49 ± 2% overall. Dry bulk density averaged 0.12 ± 0.07 g/cm3, organic matter bulk density averaged 0.11 ± 0.05 g/cm3, and total carbon content in peat averaged 47 ± 6%. In general, large differences were found between Sphagnum and non-Sphagnum peat types in terms of peat properties. Time-weighted peat carbon accumulation rates averaged 23 ± 2 (standard error of mean) g C/m2/yr during the Holocene on the basis of 151 peat cores from 127 sites, with the highest rates of carbon accumulation (25–28 g C/m2/yr) recorded during the early Holocene when the climate was warmer than the present. Furthermore, we estimate the northern peatland carbon and nitrogen pools at 436 and 10 gigatons, respectively. The database is publicly available at https://peatlands.lehigh.edu.
Keywords: biogeochemical cycles,climate change,data synthesis,long-term ecosystem dynamics,northern peatlands,soil carbon and nitrogen

Variability in exchange of CO2 across 12 northern peatland and tundra sites - Lund, M.; Lafleur, P. M.; Roulet, N. T.; Lindroth, A.; Christensen, T. R.; Aurela, M.; Chojnicki, B. H.; Flanagan, L. B.; Humphreys, E. R.; Laurila, T.; Oechel, W. C.; Olejnik, J.; et al. (Global Change Biology, 2010)
Many wetland ecosystems such as peatlands and wet tundra hold large amounts of organic carbon (C) in their soils, and are thus important in the terrestrial C cycle. We have synthesized data on the carbon dioxide (CO2) exchange obtained from eddy covariance measurements from 12 wetland sites, covering 1-7 years at each site, across Europe and North America, ranging from ombrotrophic and minerotrophic peatlands to wet tundra ecosystems, spanning temperate to arctic climate zones. The average summertime net ecosystem exchange of CO2 (NEE) was highly variable between sites. However, all sites with complete annual datasets, seven in total, acted as annual net sinks for atmospheric CO2. To evaluate the influence of gross primary production (GPP) and ecosystem respiration (R-eco) on NEE, we first removed the artificial correlation emanating from the method of partitioning NEE into GPP and R-eco. After this correction neither R-eco (P = 0.162) nor GPP (P = 0.110) correlated significantly with NEE on an annual basis. Spatial variation in annual and summertime R-eco was associated with growing season period, air temperature, growing degree days, normalized difference vegetation index and vapour pressure deficit. GPP showed weaker correlations with environmental variables as compared with R-eco, the exception being leaf area index (LAI), which correlated with both GPP and NEE, but not with R-eco. Length of growing season period was found to be the most important variable describing the spatial variation in summertime GPP and R-eco; global warming will thus cause these components to increase. Annual GPP and NEE correlated significantly with LAI and pH, thus, in order to predict wetland C exchange, differences in ecosystem structure such as leaf area and biomass as well as nutritional status must be taken into account.
635cr Times Cited:125 Cited References Count:69
Keywords: carbon carbon dioxide eddy covariance mire net ecosystem exchange peatland photosynthesis respiration tundra wetland carbon-dioxide exchange eddy covariance technique net ecosystem exchange soil respiration european forests environmental controls accumulation rates methane emissions western canada climate-change

Carbon exchange between ecosystems and atmosphere in the Czech Republic is affected by climate factors - Marek M.V.; Janouš D.; Taufarová K.; Havránková K.; Pavelka M.; V., Kaplan; I, Marková (Environmental Pollution, 2011)

An appraisal of global wetland area and its organic carbon stock - Mitra, S.; Wassmann, R.; Vlek, P. L. G. (Current Science, 2005)
Wetlands are among the most important natural resources on earth. They are the sources of cultural, economic and biological diversity. With their wealth of stored carbon, wetlands provide a potential sink for atmospheric carbon, but if not managed properly could become sources of greenhouse gases (GHGs) such as carbon dioxide and methane. Two important long-term uncertainties have initiated much debate in the scientific community. These are global wetland area and the amount of carbon stored in it. Compilation of relevant databases could be useful in setting up a long-term strategy for wetland conservation. It has been difficult to estimate the net carbon sequestration potential of a wetland, because the rate of decomposition of organic matter and the abundance of methanogenic micro-organisms and fluxes from the sediment are extremely complex, and there are often gaps in relevant scientific knowledge. The present discussion on density distribution of soil organic C in global wetlands could well be instrumental in formulating efficient strategies related to carbon sequestration and reduction of GHG emissions in wetland ecosystems. Effective assessment of wetlands will only take place when the available information becomes accessible and usable for all stakeholders.
888hl Times Cited:179 Cited References Count:66
Keywords: methane emissions atmospheric methane northern peatlands cycle soils world antarctica drainage climate model

An Assessment of NWI Maps: Implications for Wetland Protection. American Water Resources Association 2006 Spring Specialty Conference, GIS and Water Resources IV, May 8-10, 2006, Houston, Texas - Morrissey, L. A.; Sweeney, W. R. (2006)

Fluxes of nitrous oxide and methane from nitrogen-amended soils in a Colorado alpine ecosystem - Neff, J.C.; W.D. Bowman; E.A. Holland; M.C. Fisk; Schmidt, S.K. (Biogeochemistry, 1994)

The Canadian Wetland Classification System, Provisional Edition. Ecological Land Classification Series, No. 21. - National Wetlands Working Group (Canadian Wildlife Service, Environment Canada. Ottawa, Ontario, 1987)

Map Accuracy of National Wetlands Inventory Maps for Areas Subject to Maine Land Use Regulation Commission Jurisdictions, Ecological Services Report R5-94/6 - Nichols, C. (U.S. Fish and Wildlife Service: Hadley, ME, USA., 1994)

Comparison of biogenic methane emissions from unmanaged estuaries, lakes, oceans, rivers and wetlands - Ortiz-Llorente, M. J.; Alvarez-Cobelas, M. (Atmospheric Environment, 2012)

DAYCENT and its land surface submodel: description and testing - Parton, W. J.; Hartman, M.; Ojima, D.; Schimel, D. (Global and Planetary Change, 1998)
A land surface submodel was developed for the daily version of the CENTURY ecosystem model (DAYCENT). The goal of DAYCENT to simulate soil N2O, NOx, and CH4 fluxes for terrestrial ecosystems determined the structure and processes represented in the land surface model. The land surface model was set up to simulate daily dynamics of soil water and temperature from a multi-layered soil system (0-1, 1-4, 4-15, 15-30 cm, etc.) and included surface runoff and above field capacity soil water dynamics during intense rainfall events and snowmelt into frozen soils. The comparison of the simulated soil water content (0-10 cm) with observed data from four sites was quite favorable (squared correlation coefficient-gamma(2) = 0.87, 0.65, 0.86 and 0.58) and the simulated results were comparable for the soil temperature model (r(2) = 0.92 and 0.95 for minimum and maximum 10 cm soil temperatures). Detailed soil water and temperature data during snowmelt time periods and following rainfall events are needed to fully evaluate the performance of the water flow model. (C) 1998 Elsevier Science B.V. All rights reserved.
139gf Times Cited:322 Cited References Count:23
Keywords: soil water ecological models soil temperature latent heat flux daycent water flow trace gas flux shortgrass steppe model nitrification worldwide dynamics impact

A 12-year record reveals pre-growing season temperature and water table level threshold effects on the net carbon dioxide exchange in a boreal fen - Peichl, Matthias; Öquist, Mats; Ottosson Löfvenius, Mikaell; Ilstedt, Ulrik; Sagerfors, Jörgen; Grelle, Achim; Lindroth, Anders; Nilsson, Mats B. (Environmental Research Letters, 2014)

Global wetland contribution to 2000–2012 atmospheric methane growth rate dynamics - Poulter, Benjamin; Bousquet, Philippe; Canadell, Josep G.; Ciais, Philippe; Peregon, Anna; Saunois, Marielle; Arora, Vivek K.; Beerling, David J.; Brovkin, Victor; Jones, Chris D.; Joos, Fortunat; Gedney, Nicola; et al. (Environmental Research Letters, 2017)

Oil sands mining and reclamation cause massive loss of peatland and carbon storage - Rooney, R.C.; Bayle, S.E.; Shindler, D.W. (Proceedings of the National Academy Sciences USA, 2012)

Ecosystem-atmosphere exchange of CH4 and N2O and ecosystem respiration in wetlands in the Sanjiang Plain, Northeastern China - Song, C. C.; Xu, X. F.; Tian, H. Q.; Wang, Y. Y. (Global Change Biology, 2009)
Natural wetlands are critically important to global change because of their role in modulating atmospheric concentrations of CO2, CH4, and N2O. One 4-year continuous observation was conducted to examine the exchanges of CH4 and N2O between three wetland ecosystems and the atmosphere as well as the ecosystem respiration in the Sanjiang Plain in Northeastern China. From 2002 to 2005, the mean annual budgets of CH4 and N2O, and ecosystem respiration were 39.40 +/- 6.99 g Cm-2 yr(-1), 0.124 +/- 0.05 g Nm(-2) yr(-1), and 513.55 +/- 8.58 g Cm-2 yr(-1) for permanently inundated wetland; 4.36 +/- 1.79 g Cm-2 yr(-1), 0.11 +/- 0.12 g Nm(-2) yr(-1), and 880.50 +/- 71.72 g Cm-2 yr(-1) for seasonally inundated wetland; and 0.21 +/- 0.1 g Cm-2 yr(-1), 0.28 +/- 0.11 g Nm(-2) yr(-1), and 1212.83 +/- 191.98 g Cm-2 yr(-1) for shrub swamp. The substantial interannual variation of gas fluxes was due to the significant climatic variability which underscores the importance of long-term continuous observations. The apparent seasonal pattern of gas emissions associated with a significant relationship of gas fluxes to air temperature implied the potential effect of global warming on greenhouse gas emissions from natural wetlands. The budgets of CH4 and N2O fluxes and ecosystem respiration were highly variable among three wetland types, which suggest the uncertainties in previous studies in which all kinds of natural wetlands were treated as one or two functional types. New classification of global natural wetlands in more detailed level is highly expected.
404ev Times Cited:119 Cited References Count:68
Keywords: carbon dioxide ecosystem respiration methane nitrous oxide wetland fresh-water marsh methane emissions natural wetlands forest ecosystems boreal mires CO2 soil fluxes peatlands dynamics

Contrasting carbon dioxide fluxes between a drying shrub wetland in Northern Wisconsin, USA, and nearby forests - Sulman, B. N.; Desai, A. R.; Cook, B. D.; Saliendra, N.; Mackay, D. S. (Biogeosciences, 2009)

Contrasting carbon dioxide fluxes between a drying shrub wetland in Northern Wisconsin, USA, and nearby forests - Sulman, B. N.; Desai, A. R.; Cook, B. D.; Saliendra, N.; Mackay, D. S. (Biogeosciences, 2009)

An evaluation of the National Wetlands Inventory in Massachusetts - Swartwout, D.J.; MacConnell, W.P.; Finn, J.T. (The In-Place Resource Inventories Workshop. Orono, ME, USA, 1981)

Environmental control of net ecosystem CO2 exchange in a treed, moderately rich fen in northern Alberta - Syed, Kamran H.; Flanagan, Lawrence B.; Carlson, Peter J.; Glenn, Aaron J.; Van Gaalen, K. Eric (Agricultural and Forest Meteorology, 2006)

Environmental control of net ecosystem CO2 exchange in a treed, moderately rich fen in northern Alberta - Syed, Kamran H.; Flanagan, Lawrence B.; Carlson, Peter J.; Glenn, Aaron J.; Van Gaalen, K. Eric (Agricultural and Forest Meteorology, 2006)

The Impact of Climate Change on Canadian Peatlands - Tarnocai, C. (Canadian Water Resources Journal, 2009)
Peatlands cover 12% (1.136 million km(2)) of the land area of Canada, with perennially frozen peatlands covering 37% of this area and peatlands of the Boreal and Subarctic regions covering 97%. In total, these peatlands contain approximately 147 Gt of soil organic carbon, which is about 56% of the organic carbon stored in all Canadian soils. Climate change predictions suggest that the average annual air temperature in northern Canada will increase 3-5 degrees C by the end of this century. A peatland sensitivity model was used to determine the effect of climate warming on these peatlands. This model predicts that approximately 60% of the area and 56% of the organic carbon mass in all Canadian peatlands will be severely to extremely severely affected by climate change. Although peatlands were affected by climate change in the past, the changes occurred at a slower rate than is predicted for the current change of climate. This accelerated rate of climate change will result in serious degradation of perennially frozen peatlands in the Subarctic and Boreal regions and severe drying of peatlands in the southern portions of the Boreal Region. As a result of these changes, large amounts of carbon in the forms of carbon dioxide (CO(2)) and methane (CH(4)) will be released into the atmosphere from these peatlands. This will further accelerate climate warming.
Sp. Iss. SI 543og Times Cited:27 Cited References Count:47
Keywords: northwestern canada carbon permafrost accumulation variability transport manitoba mercury region

Peatlands of Canada. Open File 6561 - Tarnocai, C.; Kettles, I.M.; Lacelle, B.P. (Geological Survey of Canada, 2011)

Spatial and temporal patterns of CH4 and N2O fluxes in terrestrial ecosystems of North America during 1979–2008: application of a global biogeochemistry model - Tian, H.; Xu, X.; Liu, M.; Ren, W.; Zhang, C.; Chen, G.; Lu, C. (Biogeosciences, 2010)

Section 404 and swampbuster. In: Wetlands on Agricultural Lands. - U.S. EPA (2015)

National Wetland Condition Assessment 2011: A Collaborative Survey of the Nation’s Wetlands. EPA Report - U.S. EPA (2016)

Methane emissions from five wetland plant communities with different hydroperiods in the Big Cypress Swamp region of Florida Everglades - Villa, J. A.; Mitsch, W.J. (Ecohydrology and Hydrobiology, 2014)

Methane fluxes measured by eddy covariance and static chamber techniques at a temperate forest in central Ontario, Canada - Wang, J. M.; Murphy, J. G.; Geddes, J. A.; Winsborough, C. L.; Basiliko, N.; Thomas, S. C. (Biogeosciences, 2013)

Canadian Peatlands - Warner, B.G. (Neue Serie, 2005)

The Cambrian sedimentary characteristics and their implications for oil and gas exploration in north margin of Middle-Upper Yangtze Plate - Yu, KuanHong; Jin, ZhenKui; Su, Kui; Dong, XiaoDong; Zhang, Wei; Du, HongYu; Chen, Ying; Zhang, WeiDan (Science China Earth Sciences, 2013)

Global peatland dynamics since the Last Glacial Maximum - Yu, Zicheng; Loisel, Julie; Brosseau, Daniel P.; Beilman, David W.; Hunt, Stephanie J. (Geophysical Research Letters, 2010)

Methane emissions from global wetlands: An assessment of the uncertainty associated with various wetland extent data sets - Zhang, Bowen; Tian, Hanqin; Lu, Chaoqun; Chen, Guangsheng; Pan, Shufen; Anderson, Christopher; Poulter, Benjamin (Atmospheric Environment, 2017)
A wide range of estimates on global wetland methane (CH4) fluxes has been reported during the recent two decades. This gives rise to urgent needs to clarify and identify the uncertainty sources, and conclude a reconciled estimate for global CH4 fluxes from wetlands. Most estimates by using bottom-up approach rely on wetland data sets, but these data sets show largely inconsistent in terms of both wetland extent and spatiotemporal distribution. A quantitative assessment of uncertainties associated with these discrepancies among wetland data sets has not been well investigated yet. By comparing the five widely used global wetland data sets (GISS, GLWD, Kaplan, GIEMS and SWAMPS-GLWD), it this study, we found large differences in the wetland extent, ranging from 5.3 to 10.2 million km2, as well as their spatial and temporal distributions among the five data sets. These discrepancies in wetland data sets resulted in large bias in model-estimated global wetland CH4 emissions as simulated by using the Dynamic Land Ecosystem Model (DLEM). The model simulations indicated that the mean global wetland CH4 emissions during 2000–2007 were 177.2 ± 49.7 Tg CH4 yr−1, based on the five different data sets. The tropical regions contributed the largest portion of estimated CH4 emissions from global wetlands, but also had the largest discrepancy. Among six continents, the largest uncertainty was found in South America. Thus, the improved estimates of wetland extent and CH4 emissions in the tropical regions and South America would be a critical step toward an accurate estimate of global CH4 emissions. This uncertainty analysis also reveals an important need for our scientific community to generate a global scale wetland data set with higher spatial resolution and shorter time interval, by integrating multiple sources of field and satellite data with modeling approaches, for cross-scale extrapolation.
Keywords: Wetland Methane Uncertainty Wetland data set Tropics

Emerging role of wetland methane emissions in driving 21st century climate change - Zhang, Z.; Zimmermann, N. E.; Stenke, A.; Li, X.; Hodson, E. L.; Zhu, G.; Huang, C.; Poulter, B. (Proceedings of the National Academy of Sciences USA, 2017)
Wetland methane (CH4) emissions are the largest natural source in the global CH4 budget, contributing to roughly one third of total natural and anthropogenic emissions. As the second most important anthropogenic greenhouse gas in the atmosphere after CO2, CH4 is strongly associated with climate feedbacks. However, due to the paucity of data, wetland CH4 feedbacks were not fully assessed in the Intergovernmental Panel on Climate Change Fifth Assessment Report. The degree to which future expansion of wetlands and CH4 emissions will evolve and consequently drive climate feedbacks is thus a question of major concern. Here we present an ensemble estimate of wetland CH4 emissions driven by 38 general circulation models for the 21st century. We find that climate change-induced increases in boreal wetland extent and temperature-driven increases in tropical CH4 emissions will dominate anthropogenic CH4 emissions by 38 to 56% toward the end of the 21st century under the Representative Concentration Pathway (RCP2.6). Depending on scenarios, wetland CH4 feedbacks translate to an increase in additional global mean radiative forcing of 0.04 W.m(-2) to 0.19 W.m(-2) by the end of the 21st century. Under the "worst-case" RCP8.5 scenario, with no climate mitigation, boreal CH4 emissions are enhanced by 18.05 Tg to 41.69 Tg, due to thawing of inundated areas during the cold season (December to May) and rising temperature, while tropical CH4 emissions accelerate with a total increment of 48.36 Tg to 87.37 Tg by 2099. Our results suggest that climate mitigation policies must consider mitigation of wetland CH4 feedbacks to maintain average global warming below 2 degrees C.
Zhang, Zhen Zimmermann, Niklaus E Stenke, Andrea Li, Xin Hodson, Elke L Zhu, Gaofeng Huang, Chunlin Poulter, Benjamin eng Research Support, Non-U.S. Gov't 2017/08/23 06:00 Proc Natl Acad Sci U S A. 2017 Sep 5;114(36):9647-9652. doi: 10.1073/pnas.1618765114. Epub 2017 Aug 21.
Keywords: *climate feedbacks *climate mitigation *global warming potential *inundation *radiative forcing

Evaluation of wetland methane emissions across North America using atmospheric data and inverse modeling - Miller, Scot M.; Commane, Roisin; Melton, Joe R.; Andrews, Arlyn E.; Benmergui, Joshua; Dlugokencky, Edward J.; Janssens-Maenhout, Greet; Michalak, Anna M.; Sweeney, Colm; Worthy, Doug E. J. (Biogeosciences, 2016)

Contemporary Carbon Balance and Late Holocene Carbon Accumulation in a Northern Peatland - Roulet, Nigel T.; Lafleur, Peter M.; Richard, Pierre J. H.; Moore, Tim R.; Humphreys, Elyn R.; Bubier, Jill (Global Change Biology, 2007)